Pengaruh Edukasi Ergonomi Melalui Quizizz terhadap Pengetahuan, Sikap, Motivasi Pencegahan MSDs Tenaga Penjualan Surya Phone - Putri Bintang Adhekayana; Dwi Hendriani; Nino Adib Chifdillah; Badar Badar (Yayasan Literasi Sains Indonesia, 2026)
Musculoskeletal Disorders (MSDs) are disorders affecting muscles, joints, and supporting tissues commonly experienced by workers due to non-ergonomic working postures and repetitive activities. Low levels of knowledge, attitudes, and motivation regarding MSDs prevention indicate the need for effective and innovative occupational health education. SNI Gotrak education using Quizizz-based interactive learning media may serve as an alternative approach to improve workers’ knowledge, attitudes, and motivation toward MSDs prevention. This study aimed to determine the effect of SNI Gotrak education using Quizizz media on knowledge, attitudes, and motivation for MSDs prevention among workers. This study used a pre-experimental design with a one-group pretest–posttest approach. The sample was selected using a total sampling technique. Data were collected before and after the intervention using questionnaires on knowledge, attitudes, and motivation, and analyzed using the Wilcoxon test. The results showed an increase in respondents’ knowledge, attitudes, and motivation after the intervention. The Wilcoxon test showed a p-value < 0.05, indicating a significant difference before and after the intervention. Therefore, SNI Gotrak education using Quizizz media significantly improved workers’ knowledge, attitudes, and motivation regarding MSDs prevention.